Human stem cell-derived TRPV1-positive sensory neurons: a new tool to study mechanisms of sensitization - Schrenk-Siemens, Katrin; Pohle, Jörg; Rostock, Charlotte; Abd El Hay, Muad; Lam, Ruby M.; Szczot, Marcin; Lu, Shiying; Chesler, Alexander T.; Siemens, Jan (Cells, 2022)
Somatosensation, the detection and transduction of external and internal stimuli such as temperature or mechanical force, is vital to sustaining our bodily integrity. But still, some of the mechanisms of distinct stimuli detection and transduction are not entirely understood, especially when noxious perception turns into chronic pain. Over the past decade major progress has increased our understanding in areas such as mechanotransduction or sensory neuron classification. However, it is in particular the access to human pluripotent stem cells and the possibility of generating and studying human sensory neurons that has enriched the somatosensory research field. Based on our previous work, we describe here the generation of human stem cell-derived nociceptor-like cells. We show that by varying the differentiation strategy, we can produce different nociceptive subpopulations with different responsiveness to nociceptive stimuli such as capsaicin. Functional as well as deep sequencing analysis demonstrated that one protocol in particular allowed the generation of a mechano-nociceptive sensory neuron population, homogeneously expressing TRPV1. Accordingly, we find the cells to homogenously respond to capsaicin, to become sensitized upon inflammatory stimuli, and to respond to temperature stimulation. The efficient and homogenous generation of these neurons make them an ideal translational tool to study mechanisms of sensitization, also in the context of chronic pain.